IMPLEMENTASI PERUBAHAN UUD 1945 DAN PARADIGMA BARU - Hermoyo, Bambang (Wacana Hukum, 2011)
Abstract :New paradigma change law the basic in 1945 should bring the midset change, cultural change of the entire apparatus of state and changes in varfious regulations that do not fit anymore. Keywords : UUD 1945, paradigma, pola pikir dan kultur.